APPLICATION OF FLIPPED LEARNING METHODS IN THE UNIVERSITY CLASSROOM - Moydinova, Elmira (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
Mobile technologies have increasingly become widespread, offering convenience in our daily lives as well as significant potential for educational advancement. This case study explores university students’ satisfaction with and perceptions of the use of flipped classroom methods in foreign language learning contexts. The study employs descriptive and quantitative analysis of responses from students studying English as a foreign language at the second English faculty at the Uzbek State World Languages University (UzSWLU). The findings provide insights for educators looking to implement flipped classroom methods effectively.